MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL EKONOMI MELALUI PENERAPAN MODEL PEMBELAJARAN SIMULASI PADA SISWA KELAS VII B SEMESTER II SMP NEGERI 2 SEMARANG TAHUN 2011 - Sujarwo Sujarwo (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2011)
The students?óÔé¼Ôäó activities and achievements of?é?á class VII B at SMP N 2 Semarang dealing with the subject of economic social science have been in a lower position. The comparative measurement of lower students?óÔé¼Ôäó activities can be seen from the students?óÔé¼Ôäó attitude and understanding to the teachers?óÔé¼Ôäó explanation; the students?óÔé¼Ôäó activities in classroom, the students?óÔé¼Ôäó encouragement in conveying the arguments; the students teamwork; the students?óÔé¼Ôäó intention in classroom activity, the precise time of students in carrying out the task and the students?óÔé¼Ôäó unsystematic lesson activity. The low position of students achievement is integrated in the result of student test which has improper consequence of score minimum criteria. The condition has been becoming worse since the subject of economic social science has been excluded in the final test. The purpose of simulation learning model is to develop the students?óÔé¼Ôäó activities qualitatively and improve the students?óÔé¼Ôäó achievements quantitatively. Key Words: Simulation ?óÔé¼ÔÇ£ Activity, Economic social Science Achievement